(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of the work is to develop model and program for particle simulations working on laws of particle diffusion in expansion mode and, using approach of MonteCarlo, allows analyzing regularity in two-dimensional A+B → A reactions in case of B particle large mean free path, providing visualization of results and handy further processing of results, using data export ability. In the work are examined regularities in A+B → A reactions, special issues of these reactions, found approximate formula to determine velocity of reaction on centre of absorption surface using simulated data, developed program and made a lot of simulations of different reaction environments. Examined specific features of processed data and ways to enhance credibility and precision of results, also performed filtration of processed data to decrease specific of MonteCarlo method. Found out, that in comparison with nowadays personal computers, there is need for higher performance computing power to process simulation of particle interaction in acceptable timing.